2009
DOI: 10.1080/15376510802455347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zearalenone andα-Zearalenol in comparison with Raloxifene on T47D cells

Abstract: Zearalenone (Zen) is a mycotoxin with estrogenic effect which contaminates cereals. In cell culture, Zen and its metabolite, α-Zearalenol (α-Zel), stimulate breast cancer cells growth. Today hormone-dependent cancers are important because of high incidence and death rate. Previous studies showed that Zen and α-Zel have an effect on hormone-dependent cancers. This study explains the effects of the mentioned compounds in comparison with Raloxifene as an anti-estrogen. Cell culture technique was used with MDA-MB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Khosrokhavar et al studied the effect of raloxifene on human estrogen-receptor positive breast cancer cells T47D in combination with ZEN, a-ZAL and E 2 separately. Raloxifene inhibited cell proliferation induced by ZEN, a-ZAL and E 2 at equivalent concentrations and exhibited protective effect on cells containing estrogen receptors and significantly suppressed growth of T47D cells by about 40% (11).…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Khosrokhavar et al studied the effect of raloxifene on human estrogen-receptor positive breast cancer cells T47D in combination with ZEN, a-ZAL and E 2 separately. Raloxifene inhibited cell proliferation induced by ZEN, a-ZAL and E 2 at equivalent concentrations and exhibited protective effect on cells containing estrogen receptors and significantly suppressed growth of T47D cells by about 40% (11).…”
Section: Preventionmentioning
confidence: 99%
“…Multiple data indicate that ZEA-mediated inhibition of apoptosis is expressed in a dose-dependent manner. Khosrokhavar et al examined the effect of ZEN and a-ZEA at different concentrations on T47D (estrogen receptor-positive) and MDA-MB-231 (estrogen receptor negative) breast cancer cell lines (11). They concluded that ZEN and a-ZEA at low concentrations (Zen 10 )8 M and a-ZEA 10 )9 M ) strongly stimulated growth, providing evidence that these mycoestrogens promote the development of estrogen dependent cancer.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinogenic (breast cancer) (Khosrokhavar et al, 2009;Yu et al, 2004;Ahamed et al, 2001) and genotoxic (Lioi et al, 2004) effects of the discussed compound were also observed.…”
Section: Introductionmentioning
confidence: 69%
“…The IARC has classified aflatoxin B1 within group 1 (proven carcinogenic effect on humans) and fumonisin B1 and ochratoxin A within group 2B (possibly carcinogenic to humans) (IARC, 1993). The evidence from in vitro studies has shown that zearalenone is a probably implicated in cancer of the reproductive system (Khosrokhavar et al, 2009). …”
Section: Mycotoxinsmentioning
confidence: 99%